2017
DOI: 10.1161/circep.117.005767
|View full text |Cite
|
Sign up to set email alerts
|

Laser Balloon or Wide-Area Circumferential Irrigated Radiofrequency Ablation for Persistent Atrial Fibrillation

Abstract: https://www.clinicaltrials.org. Unique identifier: NCT01863472.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 28 publications
3
81
1
1
Order By: Relevance
“…The left atrial structural abnormalities identified by late gadolinium enhancement magnetic resonance imaging or bipolar voltage mapping (i.e., left atrial low‐voltage area, LALVA) were identified as predictors for atrial tachyarrhythmia recurrence after irrigated radiofrequency current PVI and are currently evaluated as new ablation targets . On the other hand, laser balloon (HeartLight, CardioFocus, Marlborough, MA, USA) has proven efficacy similar to irrigated radiofrequency current PVI . Theoretically, although the difference in durability of PVI between laser balloon (i.e., balloon‐based) ablation and radiofrequency current ablation remains unclear, LALVA seems to be a predictor of the atrial tachyarrhythmia recurrence even in laser balloon ablation.…”
Section: Introductionmentioning
confidence: 99%
“…The left atrial structural abnormalities identified by late gadolinium enhancement magnetic resonance imaging or bipolar voltage mapping (i.e., left atrial low‐voltage area, LALVA) were identified as predictors for atrial tachyarrhythmia recurrence after irrigated radiofrequency current PVI and are currently evaluated as new ablation targets . On the other hand, laser balloon (HeartLight, CardioFocus, Marlborough, MA, USA) has proven efficacy similar to irrigated radiofrequency current PVI . Theoretically, although the difference in durability of PVI between laser balloon (i.e., balloon‐based) ablation and radiofrequency current ablation remains unclear, LALVA seems to be a predictor of the atrial tachyarrhythmia recurrence even in laser balloon ablation.…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter trial published last year, 20 134 patients with persistent AF were randomized to undergo either laser balloon ablation or wide area circumferential PVI using radiofrequency. The freedom from AF rates was comparable between the groups (Figure 2).…”
Section: Cryoablation and Laser Balloon Ablationmentioning
confidence: 99%
“…Initial experience with Laser ablation demonstrated an acute electrical PVI success rate close to 100%, which is similar to RF . Clinical efficacy of Laser ablation in preventing AF recurrence also appears to be similar to RF and cryoablation in both paroxysmal and persistent AF . However, the PV electrical reconnection rate after Laser ablation appears to be lower than that reported for RF ablation .…”
Section: Discussionmentioning
confidence: 85%
“…In a study that was limited by the very small Initial experience with Laser ablation demonstrated an acute electrical PVI success rate close to 100%, which is similar to RF. 12,30 Clinical efficacy of Laser ablation in preventing AF recurrence also appears to be similar to RF 11,16,31 and cryoablation 14,15 in both paroxysmal 9,11,13 and persistent AF. 16,31 However, the PV electrical reconnection rate…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation